Adaptation of an architectonic traditional building: a systematic review - Wardah Fatimah Mohammad Yusoff,; Joan Atheel Ahmed,; Mohd Farid Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Taking into consideration the historical, cultural, social, and economic worth, historic structures are an essential component of the built environment. It is crucial to preserve historic structures in a sustainable manner, and to restore them so they continue to function effectively in the long run. The focus to attain standards such as BREEAM, LEED, etcetera, have been developed to fulfil more comprehensive strategic objectives when constructing new buildings, however, these requirements are insufficient when they are utilised for adjustments to older buildings. Few people are aware of the qualities of historic houses, and there are not many historic buildings that have aspects that increase their sustainability and dispel the notion that they are of lesser quality. Nonetheless, due to the unique characteristics of historic structures, it is necessary to modify and analyse the current traditional buildings and add new parameters that are not addressed by any of the grading systems under consideration. The current research aims to analyse the academic articles on design solutions for adaptability in buildings, and adaptation of an architectonic traditional building worldwide. Accordingly, this study has extracted from 24 articles that are based on a myriad of articles which have been analysed and collected from “Scopus, Web of Science, Google Scholar, IEEE, and Science Directs” under systematic literature review (PRISMA).